2021
DOI: 10.1167/tvst.10.7.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Fluorescence Lifetime Imaging Ophthalmoscopy in Atrophic Areas of Retinal Diseases

Abstract: Purpose Fluorescence lifetime imaging ophthalmoscopy (FLIO) is a non-invasive imaging modality to investigate the human retina. This study compares FLIO lifetimes in different degenerative retinal diseases. Methods Included were eyes with retinal pigment epithelium (RPE) and/or photoreceptor atrophy due to Stargardt disease ( n = 66), pattern dystrophy ( n = 18), macular telangiectasia type 2 ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…One factor potentially contributing to this sparing may be Müller glia, which survive the loss of photoreceptors 205 and retain detectable xanthophylls. 206 208 Furthermore, another analysis (365 eyes) showed that photopic visual acuity declined dramatically in relation to the amount of the remaining 1 mm-diameter central subfield. 209 Atrophy within this subfield 209 negatively correlated with visual acuity, with 34.8 letters lost if the entire subfield was affected.…”
Section: Considerations For Visual Function Testing In Geographic Atr...mentioning
confidence: 99%
“…One factor potentially contributing to this sparing may be Müller glia, which survive the loss of photoreceptors 205 and retain detectable xanthophylls. 206 208 Furthermore, another analysis (365 eyes) showed that photopic visual acuity declined dramatically in relation to the amount of the remaining 1 mm-diameter central subfield. 209 Atrophy within this subfield 209 negatively correlated with visual acuity, with 34.8 letters lost if the entire subfield was affected.…”
Section: Considerations For Visual Function Testing In Geographic Atr...mentioning
confidence: 99%
“…FLIO with blue light excitation has been demonstrated in a clinical setting, has shown changes with age and eccentricity, 22 24 and has different phenotypes with disease. 25 27 Adaptive optics FLIO (AOFLIO), which provides cellular-scale compositional and functional information has been demonstrated in vivo in mice, 28 , 29 non-human primates, 30 , 31 and humans. 32 35 With the ability to change the excitation wavelength, AOFLIO can probe contributions primarily from lipofuscin, melanin, and melanolipofuscin, AOFLIO has the potential to provide insight into in vivo cellular-scale changes with age and eccentricity.…”
Section: Introductionmentioning
confidence: 99%